The development of items for the "Inventori Persepsi bagi Muslim yang memiliki masalah pendengaran" (IPM3P) questionnaire: A prelimenary work - Rahmat, Sarah; A Rahman, Shahirah; Tukiran, Nur Hanisah; Othman, Nur Ain; Dzulkarnain, Ahmad Aidil Arafat; Musa, Ramli (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Introduction:Hearing loss is proven to affect certain area of religious life among children and student population, but there was no tool to assess its impacts on adult population. This study aims to develop a new scale in Malay to assess the perception on Islamic understanding and practice among adults with hearing impairment. It is known as ‘Inventori Persepsi bagi Muslim yang Memiliki Masalah Pendengaran’ (IPM3P).